Prevalence of Clinical Endometritis and its Impact on Reproductive Performance in Grazing Dairy Cattle in Argentina - Plöntzke, J. (2011)
The objective of this study was to evaluate the prevalence of clinical endometritis and its impact on reproductive performance in grazing dairy cattle in Argentina to compare data with previous reports from herds kept in confinement housing systems. A total of 243 Holstein dairy cows from three commercial dairy farms in Buenos Aires Province (Argentina) were examined for the signs of clinical endometritis 18–38 days postpartum (dpp) by external inspection and manual vaginal examination. Vaginal discharge was scored into the categories VDS 0 (transparent, clear mucus), VDS 1 (mucupurulent discharge), VDS 2 (purulent discharge) and VDS 3 (purulent discharge with fetid odour). Cows diagnosed with VDS 1 to VDS 3 were regarded as affected with clinical endometritis and cows with VDS 0 as free of clinical endometritis. All cows were re‐examined 14 days later following the same examination protocol. Prevalence of clinical endometritis 18–38 dpp was 35% and decreased to 18% at re‐examination. Cows with no palpable ovarian structures or periparturient disorders were at higher risk for clinical endometritis. Hazard for pregnancy was significantly lower in cows with purulent or fetid odour discharge compared with reference cows with no discharge (HR = 0.49; p = 0.01), resulting in a lower proportion of cows pregnant by 360 dpp (66% vs 78%). Furthermore, the number of services per pregnancy was higher for cows with clinical endometritis than for cows without clinical endometritis (4.4 vs 3.1; p = 0.04). Cows with clinical endometritis were 1.6 times as likely to be culled as cows with no signs of clinical endometritis. In conclusion, the prevalence and the impact of clinical endometritis in a pasture‐based, extensive dairy production system in Argentina were similar to previously published data from dairy farms with confinement production systems.